2020
DOI: 10.1088/1741-2552/abbff0
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid optogenetic and electrical stimulation for greater spatial resolution and temporal fidelity of cochlear activation

Abstract: Compared to electrical stimulation, optogenetic stimulation has the potential to improve the spatial precision of neural activation in neuroprostheses, but it requires intense light and has relatively poor temporal kinetics. We tested the effect of hybrid stimulation, which is the combination of subthreshold optical and electrical stimuli, on spectral and temporal fidelity in the cochlea by recording multiunit activity in the inferior colliculus of channelrhodopsin (H134R variant) transgenic mice. Pulsed light… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 61 publications
1
24
0
Order By: Relevance
“…Photosensitization of neurons can be achieved by optogenetics, i.e., expressing Channelrhodopsins (ChRs) in the plasma membrane of neurons (Nagel et al, 2003;Boyden et al, 2005). Optogenetic stimulation of the SGNs was shown to activate the auditory pathway (Hernandez et al, 2014;Duarte et al, 2018;Keppeler et al, 2018;Mager et al, 2018;Wrobel et al, 2018;Dieter et al, 2019Dieter et al, , 2020bKeppeler et al, 2020;Thompson et al, 2020) and to restore hearing in various models of deafness (Hernandez et al, 2014;Mager et al, 2018;Wrobel et al, 2018;Keppeler et al, 2020). Recent studies, characterizing the cochlear spread of excitation by recordings from the inferior colliculus, validate the advantage of optogenetic SGN stimulation over conventional electrical stimulation (Dieter et al, 2019(Dieter et al, , 2020bKeppeler et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Photosensitization of neurons can be achieved by optogenetics, i.e., expressing Channelrhodopsins (ChRs) in the plasma membrane of neurons (Nagel et al, 2003;Boyden et al, 2005). Optogenetic stimulation of the SGNs was shown to activate the auditory pathway (Hernandez et al, 2014;Duarte et al, 2018;Keppeler et al, 2018;Mager et al, 2018;Wrobel et al, 2018;Dieter et al, 2019Dieter et al, , 2020bKeppeler et al, 2020;Thompson et al, 2020) and to restore hearing in various models of deafness (Hernandez et al, 2014;Mager et al, 2018;Wrobel et al, 2018;Keppeler et al, 2020). Recent studies, characterizing the cochlear spread of excitation by recordings from the inferior colliculus, validate the advantage of optogenetic SGN stimulation over conventional electrical stimulation (Dieter et al, 2019(Dieter et al, , 2020bKeppeler et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although the STCs for bipolar electric stimulation were significantly narrower than those for monopolar stimulation in that study, both were substantially wider than STCs for acoustic stimulation (8.23- and 4.25-fold, respectively). Another study in mice ( Thompson et al, 2020 ) reported that STCs for electric stimulation were three to four times broader than those for pure tones. Thus, the wide spread of activation from electric stimulation measured here (3.14 times larger than that from monotones) is in good agreement with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…The temporal encoding of pulse rate with optical stimulation is not as good as with electrical or acoustic stimulation and depends strongly on the choice of opsin (Dieter et al, 2020). One interesting approach is to combine electrical and optical stimulation, leading to (in the mouse inferior colliculus) improved spatial and temporal coding compared to optical stimulation alone (Thompson et al, 2020)).…”
Section: New Alternatives To Existing Technologymentioning
confidence: 99%